Continuous production of pure maltodextrin from cyclodextrin using immobilized Pyrococcus furiosus thermostable amylase. Issue 2 (February 2016) - Cuong, Nguyen Phu; Lee, Wang-Hee; Oh, Il-Nam; Thuy, Nguyen Minh; Kim, Do-Gyun; Park, Jong-Tae; Park, Kwan-Hwa
Graphical abstract: Highlights: A packed-bed enzyme reactor (PBR) to produce pure maltodextrin from cyclodextrin was developed. Pyrococcus furiosus thermostable amylase (PFTA) was immobilized on hydrophobic resin. The immobilized PFTA remained stable during continuous process up to 25 h. Maltodextrin at high-purity (92–97%) was continuously produced using PFTA–PBR system. This study established an efficient bioconversion system for pure maltodextrin production. Abstract: Maltodextrin in specific length is of great interest because of its wide industrial applications. Previously, we have proven that Pyrococcus furiosus thermostable amylase (PFTA) produces high purity maltoheptaose (G7) from β-cyclodextrin (CD) at early reaction time. In this study, an optimal continuous process for pure maltodextrin production from CDs using PFTA with immobilization in a packed-bed reactor (PBR) was developed. For testing PBR, β-CD was used as a substrate to produce G7. The activity of immobilized PFTA in PBR retained 85% of the initial activity after 6 cycles, and the product purity was unchanged. The optimal conditions for the maximized G7-purity of 96.3% were predicted at 4.7 mL/min of flow, 1.1% substrate and 48.7 °C. Maltohexaose and maltooctaose, 92% and 97% purity respectively, were produced from CDs at the similar condition as well. Through this study, we successfully demonstrated the possibility of large-scale continuous production of pure maltodextrins from CDs.